Risk Factors for Postoperative Chylothorax Occurrence Following Pediatric Congenital Heart Surgery - Nguyen, Tran-Chau; Hoang, Thao-Vy; Nguyen, Ha-Giang; Culbertson , Casey (Journal of Humanitarian Cardiovascular Medicine, 2024)
Objectives: Chylothorax, a rare but potentially life-threatening complication post congenital heart surgery, warrants early identification of risk factors to implement preventive strategies and timely interventions. This study aims to determine risk factors associated with chylothorax occurrence at our cardiac intensive care unit. Methods: We conducted a nested case-control study involving 2042 children who underwent congenital heart surgery at Nhi Dong 1 hospital (Ho Chi Minh City, Vietnam) from Feb 25th, 2015, to October 12th, 2019. Among these, 38 chylothorax cases were matched by sex and year of surgery to 76 randomly selected control patients. Univariate analysis and logistic regression were performed to identify independent factors associated with chylothorax occurrence after congenital heart surgery. Results: Neonatal cardiac surgery, RACHS-1 risk category ≥ 3, aortic arch repair, the arterial switch operation, prolonged bypass time (median 160 mins vs 87 mins) and aortic clamp time (median 89.5mins vs 51 mins), delayed sternal closure and unexpected reoperation were all associated with postoperative chylothorax occurrence on univariate analysis. Additionally, body weight < 4.5 kg (p=0.027), postoperative dysrhythmias (p=0.004), and high volume of chest tube output (> 10% of total expected blood volume) within the first 6 postoperative hours after cardiac intensive care unit admission (p=0.014) emerged as independent risk factors for postoperative chylothorax occurrence with odds ratios and 95% confident interval of 2.78 (1.12-6.87), 3.38 (1.29-8.86) & 3.82 (1.55-9.39), respectively. These factors served as predictors of postoperative chylothorax occurrence with a sensitivity of 42.1%, specificity of 90.8%, positive predictive value of 69.6% and a negative predictive value of 75.8%. Conclusions: High chest tube output within the first 6 postoperative hours, postoperative dysrhythmias, and body weight of < 4.5kg at surgery significantly increase the risk of postoperative chylothorax in our institution. Keywords: Postoperative chylothorax, chylothorax post pediatric cardiac surgery, pediatric chylothorax